Effect of human probiotics on memory, psychological and biological measures in elderly: A study protocol of bi-center, double-blind, randomized, placebo-controlled clinical trial (CleverAge Biota) - Bartos, Ales; Weinerova, Josefina; Diondet, Sofia; Vales, Karel (Frontiers in Aging Neuroscience, 2022)
Background Gut microbiota may influence brain functions. Therefore, we prepared a study protocol for a double-blind, crossover, randomized clinical trial to determine the complex effects of human probiotics on memory, psychological, and biological measures in the elderly. Methods We selected eligible participants using an effective electronic questionnaire containing the inclusion and exclusion criteria and a brief electronic cognitive test. One-third of the respondents with the worst cognitive scores on the electronic test are randomized to group A, starting with a 3-month probiotic intervention, and to group B, starting with a placebo. In a crossover design, both groups change their intervention/placebo status after 3 months for the next 3 months. Participants refusing longer personal assessments due to the COVID-19 pandemic were randomly allocated to one of two subgroups assessed online. Participants in both groups are matched in age, education, gender, and cognitive scores on electronic testing at baseline. At three time points, participants are assessed using a neuropsychological battery, self-report measures of mood, a physical fitness test, blood, urine, and stool samples, and actigraphy. A subset of participants also provided their biological samples and underwent the neuropsychological battery in an extended testing phase 3 months after study termination to find out the long-term effect of the intervention. Discussion This is the first trial to address the comprehensive effects of human probiotics on memory and many other measures in the elderly. We assume that the probiotic group will have better outcomes than the placebo group after the first and second trimesters. We expect that the probiotic effect will persist for the next 3 months. These study’s findings will contribute to an interesting area of how to improve memory, psychological and biological and other factors naturally and will examine the importance of probiotics for overall health in the elderly. Clinical trial registration [clinicaltrials.gov], identifier [NCT05051501].